1991
DOI: 10.1161/01.str.22.8.1078
|View full text |Cite
|
Sign up to set email alerts
|

Review of the variability of the territories of the major cerebral arteries.

Abstract: The results of recent model studies indicate that the variability in territorial distribution of the major cerebral arteries may be much greater than has been previously recognized. We review the literature on the cortical and intracerebral territories of the anterior, middle, and posterior cerebral arteries. Although most authors claim that these territories are relatively consistent, the results of their studies show many and considerable discrepancies. The variability described by Beevor has been neither ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 22 publications
1
62
0
Order By: Relevance
“…For clinical implications, accurate and precise knowledge of the perfusion territories of the cerebral arteries is essential, and the delineation of individual cerebral artery flow territories is useful in evaluation of the mechanism of stroke and aids the planning of investigation and subsequent treatment. However, available maps of cerebral arterial territories are largely perfusion maps based on injection studies in cadavers (6)(7)(8).Therefore, the absence of a clear definition of the MCA territory has encouraged an alternate strategy for the development of probabilistic maps of this territory based on perfusion images. In this study, we developed the populationbased probabilistic anatomic map of the cerebral blood flow distribution of the MCA, which might have a crucial role in the assessment of cerebrovascular diseases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For clinical implications, accurate and precise knowledge of the perfusion territories of the cerebral arteries is essential, and the delineation of individual cerebral artery flow territories is useful in evaluation of the mechanism of stroke and aids the planning of investigation and subsequent treatment. However, available maps of cerebral arterial territories are largely perfusion maps based on injection studies in cadavers (6)(7)(8).Therefore, the absence of a clear definition of the MCA territory has encouraged an alternate strategy for the development of probabilistic maps of this territory based on perfusion images. In this study, we developed the populationbased probabilistic anatomic map of the cerebral blood flow distribution of the MCA, which might have a crucial role in the assessment of cerebrovascular diseases.…”
mentioning
confidence: 99%
“…For clinical implications, accurate and precise knowledge of the perfusion territories of the cerebral arteries is essential, and the delineation of individual cerebral artery flow territories is useful in evaluation of the mechanism of stroke and aids the planning of investigation and subsequent treatment. However, available maps of cerebral arterial territories are largely perfusion maps based on injection studies in cadavers (6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overestimation of the area of hypoperfusion may occur because of the delay effect (6,21,22). In addition, it is difficult to assign brain parenchyma to different arterial territories for using these AIFs (26). Further research is needed to determine whether correct rCBF can be obtained by using these two AIFs, local AIFs (25), or modified SVD techniques that are less sensitive to arrival delays, such as the block-circulant SVD technique (22) and timeshift SVD technique (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an ipsilateral AIF distal to the stenosis (6,23,24) or local AIFs (25) might be useful for the deconvolution calculation of rCBF for delayed-perfusion brain parenchyma. However, it is difficult to define arterial territories in the brain for using these AIFs (26). Due to the complexity of assimilating all the information available on parametric images, segmentation of perfusion images is valuable in providing spatiotemporal hemodynamics of local tissue perfusion.…”
mentioning
confidence: 99%